2018
DOI: 10.1111/jvs.12681
|View full text |Cite
|
Sign up to set email alerts
|

The assembly of a plant network in alpine vegetation

Abstract: Questions Positive and negative associations among species influence the structure of plant communities. Yet how these plant associations are assembled at the community level is poorly understood. We propose a new approach that combines spatial ecology, network theory and trait‐based ecology to examine the assembly of plant–plant associations at the community level. Location Gemmipass, Swiss Alps. Methods We fully mapped an alpine plant community at the individual plant level, recording both plant coordinates … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 43 publications
1
19
1
Order By: Relevance
“…When looking at spatial patterns of species distribution within communities, positive or negative species associations are based on spatial co-occurrence data that are used as a proxy for inferring positive or negative interactions among species, respectively (Burns and Zotz 2010; Saiz and Alados 2011a; Montesinos-Navarro et al 2018;Losapio et al 2018a). Contrary to plant networks based on fitness measurements, networks based on co-occurrence are representative of the spatial organisation of communities and can be expressed with different spatial resolution.…”
Section: Plant Networkmentioning
confidence: 99%
See 3 more Smart Citations
“…When looking at spatial patterns of species distribution within communities, positive or negative species associations are based on spatial co-occurrence data that are used as a proxy for inferring positive or negative interactions among species, respectively (Burns and Zotz 2010; Saiz and Alados 2011a; Montesinos-Navarro et al 2018;Losapio et al 2018a). Contrary to plant networks based on fitness measurements, networks based on co-occurrence are representative of the spatial organisation of communities and can be expressed with different spatial resolution.…”
Section: Plant Networkmentioning
confidence: 99%
“…Bayesian Networks) at community scale, including covariates that bear additional ecological information (such as abiotic conditions) and focusing on fine spatial resolution (i.e. centimetres) can help building informative plant interaction networks (Saiz et al 2017;Staniczenko et al 2017;Montesinos-Navarro et al 2018;Losapio et al 2018a).…”
Section: Plant Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…() found that the best model explaining an observed facilitation network in subtropical Brazilian forest–grasslands ecotones included species abundance but not phylogeny. Despite the relevance of plant traits determining plant–plant interactions (Losapio, de la Cruz, Escudero, Schmid, & Schöb, ; Soliveres et al., ), so far, no study has assessed the phenotypic structure of RNs to test to which extent the relevant plant traits structuring the networks are evolutionarily conserved. There has been some attempt to explain the frequency of recruitment in RNs based on the phenotype of the plants involved, showing that facilitation is stronger between species with contrasting communities of associated arbuscular mycorrhizal fungi (AMF) (Montesinos‐Navarro et al., ).…”
Section: Introductionmentioning
confidence: 99%